Determinants of Banking performance in Association of Southeast Asian Nations (ASEAN) countries - Susy Muchtar; Wahyuni Rusliyana Sari; Farah Margaretha Leon; Catur Rahayu; Suleiman Sultanali; Putra Pratama (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This study investigated the determinants of bank performance in countries belonging to the Association of Southeast Asian Nations (ASEAN). The analysis primarily included conventional banks listed on the stock exchanges of Indonesia, Malaysia, the Philippines, and Thailand from 2010 to 2019. Panel data regression was used to examine the effect of independent variables, including capital adequacy ratio (CAR), non-performing loans (NPL), loan-to-deposit ratio (LDR), market power (MP), exchange rate (ER), interest rate (IR), and technology investment (TI), on the dependent variable, bank performance. The hypothesis testing was conducted on 17 banks in Indonesia, 18 in ASEAN-3 (Malaysia, the Philippines, and Thailand), and 35 in ASEAN-4 (Indonesia, Malaysia, the Philippines, and Thailand). The results showed that CAR positively affected banks in both ASEAN-3 and ASEAN-4. NPL positively affected banks in Indonesia, while MP positively influenced banks in ASEAN-4. ER positively affected banks in Indonesia and ASEAN-3, and IR positively Influenced banks in ASEAN-4. Conversely, LDR and TI did not significantly affect any of the models. One essential contribution of this study was the inclusion of technology investment variables among other macro factors and the integration of data from various stock exchanges across ASEAN countries. These results provide a valuable theoretical framework and reference point for experts, practitioners, and banking regulators in formulating policies prioritizing bank-specific and macroeconomic variables affecting performance.